Discovery of antichagasic inhibitors by high-throughput screening with Trypanosoma cruzi glucokinase. Issue 15 (1st August 2019) - Mercaldi, Gustavo F.; D'Antonio, Edward L.; Aguessi, Annelie; Rodriguez, Ana; Cordeiro, Artur T.
Graphical abstract: Abstract: A high-throughput screening (HTS) campaign was carried out for Trypanosoma cruzi glucokinase ( Tc GlcK), a potential drug-target of the pathogenic protozoan parasite. Glycolysis and the pentose phosphate pathway (PPP) are important metabolic pathways for T. cruzi and the inhibition of the glucose kinases (i.e. glucokinase and hexokinase) may be a strategic approach for drug discovery. Glucose kinases phosphorylate d -glucose with co-substrate ATP to yield G6P, and moreover, the produced G6P enters both pathways for catabolism. The Tc GlcK – HTS campaign revealed 25 novel enzyme inhibitors that were distributed in nine chemical classes and were discovered from a primary screen of 13, 040 compounds. Thirteen of these compounds were found to have low micromolar IC 50 enzyme – inhibition values; strikingly, four of those compounds exhibited low toxicity towards NIH-3T3 murine host cells and notable in vitro trypanocidal activity. These compounds were of three chemical classes: (a) the 3-nitro-2-phenyl-2 H -chromene scaffold, (b) the N -phenyl-benzenesulfonamide scaffold, and (c) the gossypol scaffold. Two compounds from the 3-nitro-2-phenyl-2 H -chromene scaffold were determined to be hit-to-lead candidates that can proceed further down the early-stage drug discovery process.